TINJAUAN POLYESTER PADA JERSEY SEPEDA - Denta Mandra Pradipta Budiastomo; Nukke Sylvia (Universitas Mercu Buana, 2021)
This research contains the “overview of polyester on bicycle jersey”. Polyester fabric is a fabric that is often used for bicycle jerseys because it has a high coefficient of elasticity and sweat absorption which is directly channeled to the outer layer of the jersey, thus keeping the body dry and comfortable during cycling. Bike jersey is designed in such a way as to support cyclists or racers in carrying out their activities. The choice of polyester type and the difference between the Mountbike jersey and the Roadbike jersey have a role to affect the comfort while cycling because cycling with the right clothes will further increase the benefits of cycling. To study the polyester review on the bicycle jersey, the author uses qualitative methods and analysis techniques using ergonomic theory. From the results of the discussion, it can be concluded that almost all types of polyester meet the material comfort standards, but there are differences in treatment in fulfilling safety aspects.